Courage and grief : women and Sweden's Thirty Years' War - Ailes, Mary Elizabeth, 1966- (Early modern cultural studies., 2018)
Courage and Griefilluminates in a nuanced fashion Sweden's involvement in Europe's destructive Thirty Years' War (1618-48). Focusing on the various roles women performed in the bloody and extended conflict, Mary Elizabeth Ailes analyzes how methods of warfare and Swedish society were changing in profound ways. This study considers the experiences of unmarried camp followers and officers' wives as well as peasant women who remained in the countryside during times of conflict and upheaval. Women contributed to the war effort in a variety of ways. On campaign they provided support services to armies in the field. On the home front they helped to minimize disruptions incurred within their frayed communities. As increasing numbers of men left to fight overseas, women took over local economic activities and defended their families' interests. Such activities significantly altered the fabric of Swedish society. Examining women's wartime experiences in the Thirty Years' War enhances our understanding of women's roles in society, the nature of female power and authority, and the opportunities and hardships that warfare brought to women's lives.--